Analisis Strategi Keberlanjutan dalam Pengembangan Ekonomi Kreatif pada Desa Wisata di Kabupaten Buleleng - Valerie, Shannon Eunice Gretchen; M. Rudi Irwansyah (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to analyze (1) factors that influence the creative economy, and (2) sustainability strategies in the development of the creative economy in tourist villages in Buleleng Regency. This type of research is quantitative research. The population in this study amounted to 48 respondents. The determination of the number of samples used the Purposive Sampling method, namely determining the sample with certain considerations. Primary data in this study were obtained by distributing questionnaires to the head of the Tourism Awareness Group (Pokdarwis) and secondary data were obtained from related agencies such as the Buleleng Regency Tourism Office. The data obtained were then analyzed using the MICMAC and SMIC–Prob methods. The results of the study indicate that the quality of human resources, collaboration between business actors, and technology and infrastructure are key factors that greatly influence the sustainability of the creative economy. In this case, 6 scenarios have been distributed to analyze the best sustainable scenario. Scenario 1, namely the use of technology for marketing, is the best sustainable strategy because it has the highest probability of occurrence of 0.661 and the combination of "111111" with the highest probability of 0.459.